The relative importance of parasitic infections, ecoimmunological dynamics and genetic factors in determining host condition in a wild population of the house mouse, Mus musculus domesticus - Fenn, Jonathan (2019)
The factors which cause changes in condition and immune state are likely to be different in wild animals compared to inbred laboratory strains, as a result of various interacting ecological and environmental pressures not typically found under lab conditions. These include parasitic coinfection, genetic diversity, competition, ageing and seasonal changes in climate and population structure. Over the course of eight trapping sessions, ecological and morphological data from an island population of the house mouse (Mus musculus domesticus) were recorded, alongside their parasitic infections, in order to ascertain which factors impact host condition, and to what extent. The immune state of the mice was determined using multiplex ELISA to measure circulating cytokine levels, and qPCR to measure gene expression. Parasites infecting the mice were found to exist in a complex network of positive and negative associations, observed across all recorded groups of parasites. While the nematode parasites Calodium hepaticum and Trichuris muris are associated with splenic immune expression analogous to laboratory studies, parasitic infection was not a major source of variation in host condition. Seasonality was the key driver of variation in mesenteric immune expression and circulating cytokines, while SNPs within immune genes were shown to influence all measures of immune expression, and parasite community composition. Seasonality, age and immune expression were found to be the main factors associated with measures of host condition, indicating that ecological and environmental factors other than parasitic infection may be the key factors affecting fitness in this population.